2023
DOI: 10.1038/s42003-023-04592-w
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal variability of the human gut virome confounds disease signal detection in IBD

Abstract: Viruses are increasingly recognised as important components of the human microbiome, fulfilling numerous ecological roles including bacterial predation, immune stimulation, genetic diversification, horizontal gene transfer, microbial interactions, and augmentation of metabolic functions. However, our current view of the human gut virome is tainted by previous sequencing requirements that necessitated the amplification of starting nucleic acids. In this study, we performed an original longitudinal analysis of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Confirming our observations of instability of Prevotella -dominated samples, subjects from all three studies predominantly assigned to enterotype 3 (family Prevotellaceae -enriched in our designation) showed significantly greater instability (switching between enterotypes, Mann-Whitney test p values 0.024–0.047, Figures 5 C and 5D), compared to subjects predominantly assigned to enterotypes 1–2 (enriched in members of the family Bacteroidaceae , and also either Ruminococcaceae or Lachnospiraceae , Figures 5 E–5G).
Figure 5 Incubated human fecal samples and samples collected longitudinally over a period of one year can shift “enterotypes” (A) PCoA ordination of Bray-Curtis dissimilarities between incubated samples from the present study (colored circles connected by lines, 13 donors with subject 916 sampled twice, incubation time points are shown for some of the samples), longitudinally collected human fecal samples 17 (12 monthly samples from ten individuals, colored triangles), and healthy controls (n = 38) from a longitudinal IBD study 33 (3 samples collected during a year, gray crosses), all samples were processed in the same lab and sequenced using the same protocol (see STAR methods ), some donor subjects overlap between these three studies; Confidence ellipsoids represent 95% CI. (B) Bray-Curtis dissimilarities clustered using k-means method into three “enterotypes”.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirming our observations of instability of Prevotella -dominated samples, subjects from all three studies predominantly assigned to enterotype 3 (family Prevotellaceae -enriched in our designation) showed significantly greater instability (switching between enterotypes, Mann-Whitney test p values 0.024–0.047, Figures 5 C and 5D), compared to subjects predominantly assigned to enterotypes 1–2 (enriched in members of the family Bacteroidaceae , and also either Ruminococcaceae or Lachnospiraceae , Figures 5 E–5G).
Figure 5 Incubated human fecal samples and samples collected longitudinally over a period of one year can shift “enterotypes” (A) PCoA ordination of Bray-Curtis dissimilarities between incubated samples from the present study (colored circles connected by lines, 13 donors with subject 916 sampled twice, incubation time points are shown for some of the samples), longitudinally collected human fecal samples 17 (12 monthly samples from ten individuals, colored triangles), and healthy controls (n = 38) from a longitudinal IBD study 33 (3 samples collected during a year, gray crosses), all samples were processed in the same lab and sequenced using the same protocol (see STAR methods ), some donor subjects overlap between these three studies; Confidence ellipsoids represent 95% CI. (B) Bray-Curtis dissimilarities clustered using k-means method into three “enterotypes”.
…”
Section: Resultsmentioning
confidence: 99%
“…The scale of changes in bacterial communities during incubation prompted us to fit these changes into the context of the “enterotype” concept. To do that, we combined the 16S rRNA sequencing data generated here with data from a year-long longitudinal observation (monthly sampling) of fecal bacteriomes in ten individuals, 17 as well as longitudinally collected samples (three during a year for each subject, n = 38) from a healthy control cohort of a comparative IBD microbiome/virome study 33 ( Figure 5 A). Since all samples were processed in the same lab using the same protocol, and some donor subjects were enrolled in all three studies, we deemed these three datasets directly comparable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virome signature interpretation is even more difficult–longitudinal analysis has shown that the virome is less stable and shows interpersonal variability in viral taxa, frequent fluctuation of taxa even within an individual, and vast fluctuations in the abundance of temporal viruses [ 31 ]. An in-depth analysis of free virions enriched intestinal preparations showed significant enhancement of Caudovirales bacteriophages in both CD and UC [ 32 ].…”
Section: Dynamics Of Gut Ecology In Ibdmentioning
confidence: 99%
“… 39 To address this, Stockdale et al omitted the MDA step and compared results to matched 16S sequencing analyses of the same cohort. 38 They found that interindividual variation was increased using unamplified viromes, causing differences in gut virome richness between IBD and controls to be less pronounced compared with 16S sequencing. By contrast, the unamplified approach showed the opposite, with the healthy gut virome enriched in viruses compared with the IBD viromes.…”
Section: Introductionmentioning
confidence: 99%